Niger : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
The Government of the Republic of Niger has implemented the Poverty Reduction Strategy (PRS), which describes the country's macroeconomic, structural, and social policies in support of growth and poverty reduction. This strategy is based on the conviction that poverty can be reduced through strong and sustained economic growth that creates wealth and jobs. The study is the outcome of a concerted analysis. The first part outlines the diagnosis and key factors of poverty and the second part presents the major challenges, vision, overall goals, and strategic pillars.